2020
DOI: 10.1111/nicc.12561
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different syringe pumps on red cells during paediatric simulated transfusion

Abstract: Waiver of the donor's free and informed consent form was requested, as blood donation is a voluntary and altruistic act. Every donor signs a consent provided by law, in which he agrees that his blood can be used for therapeutic purposes, examinations and laboratory tests required by law and current technical standards. Therefore, it was not possible to identify the donor's origin, as the blood units did not contain the donor's identification and, thus, the donor's image and privacy were protected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Despite their benefits, the safety of this equipment in blood transfusions remains to be proven [25]; many studies have shown that SIPs can cause red cell damage during blood administration, increasing the rate of hemolysis [26]. According to health service policy, staff using volumetric infusion pumps must demonstrate knowledge and competency in using such pumps.…”
Section: Transfusion By Syringe Infusion Pumps (Sips)mentioning
confidence: 99%
“…Despite their benefits, the safety of this equipment in blood transfusions remains to be proven [25]; many studies have shown that SIPs can cause red cell damage during blood administration, increasing the rate of hemolysis [26]. According to health service policy, staff using volumetric infusion pumps must demonstrate knowledge and competency in using such pumps.…”
Section: Transfusion By Syringe Infusion Pumps (Sips)mentioning
confidence: 99%
“…Although syringe and peristaltic pumps are frequently used because of their robust flow control capabilities and compatibility with standardized components (e.g., syringes, fittings, and tubing), they can be challenging to integrate into confined environments 18 . In addition, the mechanical oscillations of the screw or cam mechanism can introduce undesired flow pulsations that result in cell damage 19 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Although syringe and peristaltic pumps are frequently used due to their robust flow control capabilities and compatibility with standardized components (e.g., syringes, fittings, and tubing), they can be challenging to integrate into confined environments. In addition, the mechanical oscillations of the rotary motor or cam mechanism can introduce undesired flow pulsations that result in cell damage (Pardo et al 2020; Kurth et al 2019; Kusahara et al 2015; Wilson et al 2016). Pneumatic pumping schemes create a defined pressure drop (Δ P ) across microfluidic networks to drive fluid flows.…”
Section: Introductionmentioning
confidence: 99%